Becoming Mongrel:: Grotesque Complicity in Don LePan’s Animals - Keen, Paul (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
Don LePan’s novel Animals, a dystopian account of a future gone wrong, is an animal story with an ironic twist. Featuring no actual animals – indeed, set at a time when there are virtually no animals left on the planet, Animals is driven by narrative tensions that disrupt enduring forms of speciesism and highlight the simultaneous necessity and impossibility of such categories. The novel converges with the efforts of posthumanist critics like Cary Wolfe, Jodey Castricano, and Donna Haraway in its depiction of the human/non-human divide and in its insistence on the philosophical necessity of including non-human animals in the designation of the Other to whom we remain morally responsible. In this sense, Sam’s experience of becoming mongrel – his descent from human, to mongrel, to raw material for consumption – epitomizes the broader dehumanization of an entire culture. By inviting readers to judge the decisions characters make in reinforcing and policing the constructed categories of mongrels and humans, LePan questions the unstable classificatory systems through which we organize physical and textual worlds.